Long term persistence of introduced Amblyomma geoemydae tick population under indoor conditions in Austria - Bilbija, B; Auer, M; Široký, P (Medical and veterinary entomology, 2019)
An indoor terrarium population of Amblyomma geoemydae was established subsequent to the import of a single yellow-marginated box turtle Cuora flavomarginata. This indoor tick population revealed an unexpected resistance against de-ticking trials, with persistence between 2010 and 2015, when the ticks were successfully eliminated. Ticks were collected from the bodies and shells of turtles, as well as from terraria soil. Species diagnosis of ticks was carried out according to distinguishable morphological characters and supported by molecular analysis using DNA-barcoding. Introduced exotic ticks are potential vectors of pathogens and can have an impact on wildlife, domestic animals and the human population. This case emphasizes the need for sharp surveillance and control measures on imported reptiles.
Keywords: reptile ticks; Nymph; taxonomické DNA čárové kódování; DNA Barcoding, Taxonomic; zvířata v ZOO; Ixodidae; Geoemyda; larva; Female; zvířata; Rakousko; Japan; spread exotic ticks; nymfa; Austria; roční období; ženské pohlaví; Animals, Zoo; Seasons; želvy; infestace klíšťaty; zavlečené druhy; Turtles; Cuora; Amblyomma geoemydae; Larva; Animals; Tick Infestations; Introduced Species